Evaluation of systemic immune-inflammation index and systemic inflammation response index in the differentiation of acute Ischemic stroke and transient Ischemic attack - Yilmaz, Mustafa; Uslu, Muhammad Fuad; Atescelik, Metin; Atilgan, Fethi Ahmet (Kamuzu Univ Health Sciences - Kuhes, 2024)
Objective The aim of this study was to examine the levels of hematologic parameters in acute ischemic stroke (AIS) and transient ischemic attack (TIA) and to evaluate the use of Neutrophil/Lymphocyte ratio (NLR), Systemic Immune-Inflammation Index (SII), and systemic inflammation response index (SIRI) in the differentiation of AIS and TIA. Materials and Methods Data and hematological results of patients admitted to the emergency department and diagnosed with AIS and TIA were compared retrospectively. Results The study included 36 TIA patients (M/F = 15/21) with a mean age of 64.52 +/- 15.597 years and 74 AIS patients (M/F = 35/39) with a mean age of 71.91 +/- 13.86 years. Laboratory data showed that lymphocyte count (p = 0.022) and hemoglobin level (p = 0.017) were significantly higher in AIS patients. In addition, monocyte count (p = 0.001), neutrophil/lymphocyte ratio (NLR) (p < 0.001), CRP level (p = 0.007), and SII (p = 0.001) and SIRI values ( < 0.001) were significantly increased in AIS patients compared to TIA patients. Conclusion The results obtained in the present study show that hematologic inflammatory parameters are increased in AIS. NLR, SII and SIRI may provide insight in the differential diagnosis of AIS and TIA.
Keywords: Acute ischemic stroke; Transient ischemic attack; Systemic Immune-Inflammation Index; Systemic inflammation response index; & Idot;nflammatory response; Hemorrhage